A Good Story Well Told: Storytelling Components That Impact Science Video Popularity on YouTube - Huang, Tianle; Grant, Will J. (Frontiers in Communication, 2020)
Storytelling plays a crucial role in science communication, but little research has investigated how it impacts the popularity of science videos. This study examined storytelling components in 306 popular YouTube science videos and revealed significant relationships between video popularity and five storytelling components, namely dramatic question, insight, moments of change, emotional arousal and status of story. Emotional arousal, in particular, showed a strong association with popularity. The results shed light on the role of storytelling in increasing science video popularity.